A critical review of research on technological pedagogical and content knowledge (TPACK) in language teaching. Issue 4 (4th May 2022) - Tseng, Jun-Jie; Chai, Ching Sing; Tan, Lynde; Park, Moonyoung
Abstract: Research on TPACK has been burgeoning recently. Some review studies in the field of educational technology have indicated issues and trends in TPACK research conducted in the past decades. However, a review of TPACK research specific to language teachers' knowledge about language teaching with technology has been lacking. To fill this research gap, the present review study intends to understand the landscape of TPACK research on language teachers published from 2011 to 2019. The analysis results reveal that 51 studies were identified with a publication peak in 2015, mostly conducted in Asia and the Middle East. The 51 articles were categorized into four areas: (a) exploring TPACK, (b) assessing TPACK, (c) developing TPACK, and (d) applying TPACK. More specifically, research on exploring TPACK suggests that while teachers had varying levels of confidence in their TPACK competence, their TPACK indicated the dominant use of technology in traditional teacher-centered teaching. Research on assessing TPACK shows that survey items were contextualized to lessen the difficulty of distinguishing between the seven sub-domains of TPACK. However, the difficulty remained perhaps due to a possibility that the seven sub-domains may not appear workable in practice. This issue needs further research. Research on developing TPACK reveals that effective interventions involved language teachers' understanding of the TPACK framework, modeling from teacher educators or experienced teachers, and language teachers' engagement in designing lessons collaboratively. Finally, research on applying TPACK indicates that TPACK-informed language learning courses and platforms were perceived to be helpful and effective. These findings may provide researchers with some possible directions.